2008
DOI: 10.1016/j.expneurol.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics and morphology of regenerating optic fibers in tectum are altered by injury conditions: An in vivo imaging study in goldfish

Abstract: The dynamic behavior of axons in systems that normally regenerate may provide clues for promoting regeneration in humans. When the optic nerve is severed in adult goldfish, all axons regenerate back to the tectum to reestablish accurate connections. In adult mammals, regeneration can be induced in optic and other axons but typically few fibers regrow and only for short distances. These conditions were mimicked in the adult goldfish by surgically deflecting 10-20% of optic fibers from one tectum into the opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…En general las fibras del nervio óptico inervan el tectum óptico (TO) desde la región media hasta la posterior (Johnson et al, 1999). Específicamente la región ventronasal de la retina inerva el tercio medio o el tercio posterior del tectum óptico y la lamina óptica en goldfish (Dawson & Meyer, 2008). Esto sugiere que las diferentes subpoblaciones de fibras en el nervio óptico de A. seemanni podrían corresponder a la inervación en diferentes regiones del tectum, generando una topografía específica en esa estructura.…”
Section: Discussionunclassified
“…En general las fibras del nervio óptico inervan el tectum óptico (TO) desde la región media hasta la posterior (Johnson et al, 1999). Específicamente la región ventronasal de la retina inerva el tercio medio o el tercio posterior del tectum óptico y la lamina óptica en goldfish (Dawson & Meyer, 2008). Esto sugiere que las diferentes subpoblaciones de fibras en el nervio óptico de A. seemanni podrían corresponder a la inervación en diferentes regiones del tectum, generando una topografía específica en esa estructura.…”
Section: Discussionunclassified
“…For instance, DiI was used in studies of axonal regrowth following crush injury to entire CNS of embryonic rat (Saunders et al, 1992) or neonatal opossum (Treherne et al, 1992) maintained in culture. In vivo assays of axonal regeneration are also facilitated by the use of lipid‐soluble dyes such as those of optic fibers regenerate in the goldfish (Dawson and Meyer, 2001, 2008) and in the Xenopus tadpole (Vergara and Del Rio‐Tsonis, 2009).…”
Section: Dye‐mediated Labeling Techniquesmentioning
confidence: 99%
“…Simultaneous imaging of RGCs and subpopulations of presynaptic amacrine interneurons over a period of days revealed that RGC dendrites targeted amacrine plexuses 20. The dynamic behaviour of axons can also be studied by intraretinal injection of the fluorescent carbocyanine dye DiI in goldfish and image acquisition using a fluorescence microscope equipped with rhodamine optics 21. In rodents, in vivo imaging of RGCs can be much more readily achieved by using transgenic mice that express CFP under the control of a Thy-1 promoter construct, and modified cSLO 22.…”
Section: Imaging Techniques and Devicesmentioning
confidence: 99%